2008
DOI: 10.1128/jb.01766-07
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Chromate Reductase from Thermus scotoductus SA-01 Related to Old Yellow Enzyme

Abstract: Bacteria can reduce toxic and carcinogenic Cr(VI) to insoluble and less toxic Cr(III). Thermus scotoductus SA-01, a South African gold mine isolate, has been shown to be able to reduce a variety of metals, including Cr(VI). Here we report the purification to homogeneity and characterization of a novel chromate reductase. The oxidoreductase is a homodimeric protein, with a monomer molecular mass of approximately 36 kDa, containing a noncovalently bound flavin mononucleotide cofactor. The chromate reductase is o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
118
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 155 publications
(123 citation statements)
references
References 34 publications
4
118
1
Order By: Relevance
“…To date, the best-studied chromate reductase is ChrR, a soluble, dimeric, NADH-dependent flavoprotein reported in Pseudomonas putida (38,39). BLASTP searches of the strain HCF1 genome were conducted for the following chromate reductases: ChrR from P. putida (GenBank accession number AF375642); an Old Yellow Enzyme (OYE) homolog from Thermus scotoductis (GenBank accession number AM902709 [40]); YieF, a ChrR homolog from E. coli (GenBank accession number AAK62985.2 [38]); the Fre flavin reductase from E. coli (EcoCyc accession number EG10334 [25]); FerB from Paracoccus denitrificans (putatively GenBank accession number YP_917833.1 [41,42]); and an azoreductase from Bacillus sp. OY1-2 (GenBank accession number BAB13746.1 [43]).…”
Section: Resultsmentioning
confidence: 99%
“…To date, the best-studied chromate reductase is ChrR, a soluble, dimeric, NADH-dependent flavoprotein reported in Pseudomonas putida (38,39). BLASTP searches of the strain HCF1 genome were conducted for the following chromate reductases: ChrR from P. putida (GenBank accession number AF375642); an Old Yellow Enzyme (OYE) homolog from Thermus scotoductis (GenBank accession number AM902709 [40]); YieF, a ChrR homolog from E. coli (GenBank accession number AAK62985.2 [38]); the Fre flavin reductase from E. coli (EcoCyc accession number EG10334 [25]); FerB from Paracoccus denitrificans (putatively GenBank accession number YP_917833.1 [41,42]); and an azoreductase from Bacillus sp. OY1-2 (GenBank accession number BAB13746.1 [43]).…”
Section: Resultsmentioning
confidence: 99%
“…The model biocatalyst was the old yellow enzyme homologue from Thermus scotoductus SA-01 (TsOYE) 40,41 , catalysing the stereoselective trans-hydrogenation of Ketoisophorone (1) to (R)-Levodione (2) (Fig. 2).…”
Section: Photobiocatalytic Reduction Reactionsmentioning
confidence: 99%
“…The optimum temperature of the partially purified enzyme was determined by incubating the reaction mixture of the enzyme at different temperatures ranging from 30 ºC to 90 ºC for 10 min. In order to determine the effects of pH on the stability of the enzyme, the partially purified enzyme protein was exposed to various pHs (6)(7)(8) …”
Section: Effect Of Ph and Temperaturementioning
confidence: 99%
“…In aerobic conditions, the enzyme chromate reductase is reported to reduce Cr(VI) to Cr(III) inside or outside the plasma membrane and utilize NADH as electron donor, while under anaerobic condition membrane bound chromate reductase reduces Cr(VI) through respiratory chains involving cytochromes [3][4][5]. The most efficient Cr(VI) transforming enzymes that have been described to date are flavo-proteins, but these require expensive NADPH cofactors to power reduction, and stoichiometric addition of these cofactors is not an economically viable proposition for large scale applications [6][7][8][9][10]. Das and Chandra [11] have reported that Cr(VI) was reduced to Cr(III) in the presence of NADPH in the cell extract of Streptomyces species and existence of NADPH-dependent chromium (VI) reductase in Pseudomonas ambigua G-1, E.coli [12,13].…”
Section: Introductionmentioning
confidence: 99%